2018
DOI: 10.1016/j.jor.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Insufficiency fracture at an osteochondroma bridging the proximal fibula and the tibia: Case report

Abstract: Osteochondromas are benign bone tumors that protrude from underlying bone. A fracture of an osteochondroma is rare, and no insufficiency fractures of an osteochondroma have been reported. A 57-year-old female complained of pain in her proximal leg that increased during walking. A computed tomographic image depicted bridging that had extended to the tibia. An incomplete fracture line was observed at the osteochondroma. The osteochondroma was resected to remove the bridge. The preoperative symptoms disappeared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Mendelson et al 9 reported on an 89-year-old woman with a proximal tibia and fibula fragility fracture in 2011. Cheung et al 10 reported on an 82-year-old man who experienced an insufficiency fracture of the proximal fibula and the tibia in 2013. There is a need for a clear definition of PTFF that accurately describes its anatomy and scope and is universally applicable in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Mendelson et al 9 reported on an 89-year-old woman with a proximal tibia and fibula fragility fracture in 2011. Cheung et al 10 reported on an 82-year-old man who experienced an insufficiency fracture of the proximal fibula and the tibia in 2013. There is a need for a clear definition of PTFF that accurately describes its anatomy and scope and is universally applicable in adults.…”
Section: Introductionmentioning
confidence: 99%